Microbiota Diversity in Pearl Oyster Pinctada fucata martensii Intestine and Its Aquaculture Environment - Zheng, Zhe; Liao, Yongshan; Ye, Jianming; Yang, Chuangye; Adzigbli, Linda; Wang, Qingheng; Du, Xiaodong; Deng, Yuewen (Frontiers in Marine Science, 2021)
Environmental microbiota plays a vital role in the intestinal microbiota of aquatic organisms. However, data concerning the association between the intestinal microbiota of pearl oyster Pinctada fucata martensii and the surrounding seawater are limited. The existing bacterial communities in pearl oyster intestine and surrounding water from two sites (D and H, within Liusha Bay in Guangdong, China) were investigated using 16S rRNA-based sequencing to explore the relationship among the two. D located in the inner bay, and H located in the open sea area outside bay. Results revealed the richness and diversity of pearl oyster intestinal microbiota to be less than those of the surrounding water, with 38 phyla and 272 genera observed as a result of the classifiable sequence. The microbiota compositions in the intestine and the surrounding water were diversified at the phylum and genus levels, with the sequencing data being statistically significant. However, the functional prediction of microbiota emphasized the overall similarity in the functional profile of the surrounding seawater and intestinal microbiomes. This profile was associated with metabolism of cofactors and vitamin, carbohydrates metabolism, amino acids metabolism, metabolism of terpenoids and polyketides, metabolism of other amino acids, lipids metabolism, and energy metabolism. Seven common operational taxonomic units (OTUs), which belonged to phyla Tenericutes, Cyanobacteria, and Planctomycetes, were noted in the intestines of pearl oysters from two different sites. These OTUs may be affiliates to the core microbiome of pearl oyster. Significantly different bacterial taxa in the intestines of pearl oysters from two different sites were found at the phylum and genus levels. This finding suggested that the bacterial communities in pearl oyster intestines may exhibit some plasticity to adapt to changes in the surrounding water-cultured environment. This study generally offers constructive discoveries associated with pearl oyster intestinal microbiota and provides guidance for sustainable aquaculture.